Educational Background Occupation Distribution In Viral Skin Infection Patients At Dermatology And Venereology Outpatient Clinic Dr. Soetomo General A Cademic Hospital Surabaya From January 2019-December 2021 - Alya Nuha Andini; Linda Astari; Musofa Rusli; Medhi Denisa (Sean Institute, 2024)
The total cases of viral skin infections in Indonesia, coupled with a lack of awareness regarding the associated risk factors and preventive measures, poses a significant issue. There is a scarcity of research addressing the profile of viral skin infections in Indonesia. This study aims to assess the distribution of educational background and occupation of patients with viral infections treated at the Dermatology and Venereology Outpatient Unit of Dr. Soetomo General Hospital in Surabaya from 2016 to 2018. Using a descriptive approach, this retrospective study relies on medical records spanning from January 2019 to December 2021. The majority of patient’s last educational background was senior high school. (43%), with the diagnosis of herpes simplex dominated by senior high school (57%), molluscum contagiosum by patients that never went to school (29%), varicella by both senior high school and patients that never went to school (29%), and herpes zoster by senior high school (30%). The majority of patients work as private employees (28%), with the diagnosis of herpes simplex patients work as college student (29%), Molluscum contagiosum as college student (25%), varicella as college student (30%), and herpes zoster as private employees (35%). In conclusion, the distribution of educational background and occupation of viral skin infection patients at Dermatology and Venereology Outpatient Clinic Dr. Soetomo General Academic Hospital Surabaya from January 2019 - December 2021 still varies every year and requires more comprehensive management.